Has India’s Economic Growth Become More Pro-Poor in the Wake of Economic Reforms? - Datt, Gaurav; Ravallion, Martin (World Bank, 2013)
The extent to which India's poor have benefited from the country's economic growth has long been debated. A new series of consumption-based poverty measures spanning 50 years, including a 15-year period after economic reforms began in earnest in the early 1990s, is used to examine that issue. Growth has tended to reduce poverty, including in the postreform period. There is no robust evidence of more or less poverty responsiveness to growth since the reforms began, although there are signs of rising inequality. The impact of growth is higher when using poverty measures that reflect distribution below the poverty line and when using growth rates calculated from household surveys rather than national accounts. The urban-rural pattern of growth matters for the pace of poverty reduction. However, in marked contrast to the period before the reforms, urban economic growth in the period after the reforms has brought significant gains to the rural poor as well as the urban poor.